When Do We Repair the Roof? : Insights from Responses to Fiscal Crisis Early Warning Signals - Honda, Jiro.; Issifou, Ismael; Tapsoba, Rene. (Washington, D.C. : International Monetary Fund, 2018)
Should policymakers wait for fiscal crisis early warning signals before repairing the roof? We give an answer to this question by investigating the interlinkages between early warning signals for fiscal crisis, policy responses, and policy outcomes, using a broad panel of 119 countries. We find that fiscal adjsutment is a good remedy for countries that act proactively, reducing their likelihood of facing fiscal crisis by up to about 60 percent. For those waiting for wake-up calls from early-detection tools, however, fiscal adjustment may not fully prevent fiscal crisis occurrence, with the chance of fiscal crisis prevention not only smaller (about 30 percent) but also statistically not significant. These findings highlight the prominence of repairing the roof when the sun is shining, particularly in countries with weak institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet